Evaluation Drinking Water in the Pediatrics and Kirkuk Educational Hospitals Within City of Kirkuk - Nadya Esmaeel Mustafa; Riedh Abass Abdul Jabbar; Mahmood K. Saleh (Tikrit Journal of Pure Science, 2025)
The study involved collecting drinking water samples from Kirkuk Teaching Hospital (A) and the Hospital of Pediatrics (B), with three sampling sites in each hospital. Sampling occurred once a month from 8:00 AM to 2:00 PM, starting from September 2022 until January 2023. The biological examination involved culturing blood agar and Mannitol salt agar to detect Staphylococcus aureus bacteria, but none were found. Instead, other bacteria appeared, which were not the focus of our study. These included three types: Kocuria rosea, Kocuria rhizophila, Kocuria kristinae, Alloiococcus otitidis, and Serratia marcescens. Physicochemical tests conducted included temperature (T), pH value (pH), electrical conductivity (EC), biochemical oxygen demand (BOD5), and total dissolved solids (TDS). Temperature and pH levels were within the natural range recommended by the World Health Organization. However, the biochemical oxygen demand was very high in both hospitals, and total dissolved solids were within the natural range at Kirkuk Teaching Hospital (A) but were elevated at the Hospital of Pediatrics (B) in September only.